THE COMPOSITION OF LIQUIDS COEXISTING WITH DENSE HYDROUS MAGNESIUM SILICATES AT 11-13.5 GPA AND THE ENDPOINTS OF THE SOLIDI IN THE MGO-SIO2-H2O SYSTEM - Melekhova E.; Schmidt M.W.; Ulmer P.; Pettke T. (My University, 2007)
High-pressure liquids in the MgO-SiO2-H2O (MSH) system have been investigated at 11 and 13.5 GPa and between 1000 and 1350 °C. A bulk composition more magnesian than the tie-line forsterite-H2O was employed for the study. Rocking multi-anvil experiments were combined with a diamond trap set-up. After termination of the experiments, the liquid trapped in the diamond layer was analysed by laser ablation ICP-MS using the 'freezing' technique. At 11 GPa, liquids coexist with one or two of phase A, clinohumite, chondrodite, and forsterite. A marked discontinuity in the evolution of liquid compositions near 1100 °C is observed at 11 GPa. A step of ~13 wt% H2O and 13 wt% MgO is interpreted to result from overstepping the fluid-saturated solidus reaction mass balanced to 1.00(18) phase A + 1.07(4) fluid = 0.63(15) chondrodite + 1.44(2) melt. At 13.5 GPa liquids coexist with one or two of hydrous wadsleyite, clinohumite, superhydrous B, phase B, and forsterite. The discontinuity in liquid composition is no longer present, indicating that the second critical endpoint of the solidus has been overstepped. Thus, hydrous melts in the Mg-rich part of the MSH system (molar bulk Mg/Si > 2) are chemically distinct from aqueous fluids at pressure up to 11 GPa. Convergence of fluid and melt compositions along the solidus resulting in a supercritical liquid occurs between 11 and 13.5 GPa, at which pressure the entire MSH system becomes supercritical. © 2007 Elsevier Ltd. All rights reserved.
Keywords: MgO–SiO2–H2O system